ORGANIZATIONAL CULTURE AS A STRATEGIC LEVER: A SYSTEMATIC REVIEW OF ITS IMPACT ON ORGANIZATIONAL PERFORMANCE - Muhammad Maulana Ibrahim; Ig Jarot Febri Setyo Wibowo; Sopiah (RADJA PUBLIKA, 2025)
Organizational culture has undergone a role shift, transitioning from being perceived as a normative dimension to becoming a strategic factor that determines the success of strategy implementation and organizational performance. This study aims to conduct a systematic review of the relationship between organizational culture, strategic levers, and organizational performance by referencing literature from the past five years. The method employed is a Systematic Literature Review (SLR) following the PRISMA 2020 protocol, analyzing 40 articles from reputable Scopus-indexed journals (Q1-Q4). The synthesis results indicate that organizational culture forms a value-based foundation that influences the structure and function of strategic levers, which indirectly strengthens organizational performance achievement. This study produces a conceptual framework mapping the culture-strategy-performance linkage and identifies research gaps in methodological dimensions, micro-level contexts, and culture-strategy synergy. Theoretically, this study enriches the Resource-Based View and Strategic Fit Model approaches. Practically, the findings provide guidance for managers in designing mutually supportive cultural and strategic systems. Future research is recommended to explore longitudinal approaches, mixed methods, and cross-cultural studies.